Refinement of high-spatial resolution U-Pb geochronological methodologies - Corbett, Eoghan Paraic (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2021)
Zircon [ZrSiO4] is a naturally occurring mineral commonly used in geochronological, isotope and elemental geochemical studies. It can form as an accessory phase in a wide variety of magmatic and metamorphic conditions and is remarkably stable both physically and chemically over geological timescales. It will often reliably preserve isotopic and geochemical information even under extreme pressure and temperature conditions. If a zircon remains isotopically undisturbed since its initial closure (i.e. crystallisation), an absolute age for its formation can be determined by the U-(Th-)Pb (parent/daughter) ratio. However, owing to its incorporation of tandem uranium (238U → 206Pb) and actinium-series (235U → 207Pb) decay schemes, it is also possible to determine instances when the integrity of its U-Pb systematics were compromised in the past. In addition to its incorporation of radionuclides, zircon also has a tendency to incorporate useful temperature- or process-sensitive trace elements, including the rare earth elements (REE), yttrium (Y) and titanium (Ti). A discrete record of age, temperature and process histories within zircon is often preserved within sharply defined and compositionally distinct intra-crystalline zones/domains which occur at a micron to sub-micron scale and which can only be sampled using in-situ high-spatial resolution techniques. Chapter 2 of this thesis contributes directly to the field of high-spatial resolution techniques, by the application of a novel method of high-resolution in-situ zircon U-Pb determination, which dramatically reduces the crater depth by comparison with conventional, high-frequency static laser ablation protocols (by up to 96.5%) and produces ages indistinguishable from those derived by benchmark isotope-dilution thermal ionisation mass-spectrometry (ID-TIMS). The approach to laser ablation analysis described herein, in addition to improving the depth-resolution of analysis, may help to overcome downhole fractionation and plasma loading effects. The second study of this thesis contained in chapter 3, contributes towards an improved understanding of processes occurring during laser sampling of zircon. It presents the likely cause of a zircon matrix-dependent bias present in U-Pb age determination by LA-ICP-MS, which becomes apparent in a comparison of mirrored halves of the same Ple ovice zircon crystal in which one half has been subjected to an artificial annealing process at 1100˚C for 96 h. A comparison of equivalent sampling locations reveals a poor approximation of the laser spot mask, sub-parallel crater walls and non-stoichiometric U-Pb sampling within the annealed matrix. We propose that relative changes in the optical and thermo-physical properties of the annealed zircon matrix are responsible for the systematic offset towards younger apparent ages, away from the accepted age by ~22 Ma (i.e. 6.7%). The final contribution of this thesis (Chapter 4) examines the phenomenon of anomalous apparent age distribution within zircon which has experienced multiple metamorphic episodes. Recrystallisation of radiation damage domains occurs in the wake of an inwardly progressing reaction front catalysed by the percolation of fluids. As a result, the recorded age information, has been decoupled from the expected core-to-rim textural succession of growth usually observed under cathodoluminescence (CL). The viability of two potential fluid-mediated mechanisms for intra-crystalline element mobilisation is considered with respect to numerous textural, chemical, micro-structural, and isotopic observations, which when combined contributes to an understanding of how partial resetting of isotope systematics in zircon may occur. A recognition of the characteristic features associated with such a process, allows for reacted and un-reacted domains to be distinguished thereby allowing meaningful ages (pertaining to discrete intra-crystalline domains) to be determined from zircons, which might otherwise be disregarded in an analysis of such rocks.
APPROVED
Keywords: U-Pb; Zircon; Laser Ablation; Mass Spectrometry; LA-ICP-MS; High-spatial resolution; Radiation damage